Analisis Pertumbuhan Kinerja Keuangan Perbankan dengan Menggunakan Analisis CAMEL (Studi pada Bursa Efek Indonesia Tahun 2016–2018) - Kainama, Frilya Enjels; Kainama, Maryoni Stevanny; Tomasoa, Theodora Florence (Jurnal Pendidikan Ekonomi, 2023)
Bank financial performance is crucial for supporting economic stability and the smooth functioning of financial intermediation. This study aims to analyze the growth of banking financial performance on the Indonesia Stock Exchange for the period 2016–2018 using the CAMEL analysis, which includes capital, asset quality, management effectiveness, earnings, and liquidity. The research employed a descriptive quantitative method, utilizing secondary data from the annual financial reports of 35 banks selected through purposive sampling. The results indicate that the growth of banking financial performance varies across each CAMEL aspect. Some banks showed positive growth in capital, management effectiveness, and liquidity, but not all were able to consistently reduce the risk of non-performing loans. These findings illustrate that financial performance among Indonesian banks is still uneven and optimization in risk management and operational efficiency is needed. The implication is that banks must strengthen their capital base and enhance risk management systems to maintain competitiveness and foster sustainable growth in the banking industry